1995
DOI: 10.1897/1552-8618(1995)14[415:ctsosa]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Toxicant Sensitivity of Sexual and Asexual Reproduction in the Rotifer Brachionus Calyciflorus

Abstract: Cyclically parthenogenetic zooplankters like rotifers are important tools for assessing toxicity in aquatic environments Sexual reproduction is an essential component of rotifer life cycles, but current toxicity tests utilize only asexual reproduction We compared the effects of four toxicants on asexual and sexual reproduction of the rotifer Brachionus calyciflorus Toxicants had a differential effect on sexual and asexual reproduction, with sexual reproduction consistently the most sensitive Concentrations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
50
1
2

Year Published

1997
1997
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 15 publications
9
50
1
2
Order By: Relevance
“…Regardless of the mechanisms driving this trend, our results suggest that significant toxicological effects may be observed in parameters related to the production and quality of diapausing eggs, although gross endpoints, such as population growth rate, are insensitive to toxicants. In rotifers there is broad evidence that the sexual phase can be more sensitive to environmental conditions, specifically exposure to toxicants, than the asexual phase (Snell and Carmona 1995;Snell et al 1999;Preston and Snell 2001;Marcial et al 2005). Our results are in agreement with those antecedents, but in addition this study provides interesting information about the adaptive value of the diapause strategy against adverse conditions.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Regardless of the mechanisms driving this trend, our results suggest that significant toxicological effects may be observed in parameters related to the production and quality of diapausing eggs, although gross endpoints, such as population growth rate, are insensitive to toxicants. In rotifers there is broad evidence that the sexual phase can be more sensitive to environmental conditions, specifically exposure to toxicants, than the asexual phase (Snell and Carmona 1995;Snell et al 1999;Preston and Snell 2001;Marcial et al 2005). Our results are in agreement with those antecedents, but in addition this study provides interesting information about the adaptive value of the diapause strategy against adverse conditions.…”
Section: Discussionsupporting
confidence: 84%
“…Nevertheless, because only the asexual portion of the life cycle is commonly investigated in toxicity studies, the true vulnerability of zooplankton to toxicants is often underestimated (Preston and Snell 2001;Navis et al 2015). Several studies assessed the effects of pesticides, heavy metals, and endocrine-disrupting chemicals on sexual reproductive parameters of rotifers (Snell and Carmona 1995;Preston et al 2000;Yoshinaga et al 2000;Preston and Snell 2001;Radix et al 2002;Marcial et al 2005;Ríos-Arana et al 2007) and cladocerans (Tatarazako and Oda 2007;Navis et al 2013Navis et al , 2015. Their results showed that, depending on the species and contaminants tested, reproductive parameters such as mixis ratio (i.e., proportion of sexual females relative to all females, sexual and asexual) and fertilization, and diapause parameters such as resting egg production and resting egg hatchability are among the most sensitive endpoints to assess toxicity in zooplankton species.…”
Section: Introductionmentioning
confidence: 99%
“…There is an alternation of parthenogenic and sexual reproduction in the life cycle of rotifers (Snell and Carmona, 1995). At the beginning of the growing season, diploid parthenogenic females hatch out from the RE of the previous season.…”
Section: Introductionmentioning
confidence: 99%
“…Parthenogenic females reproduce unisexually by laying diploid eggs, which develop into females. Upon receiving appropriate environmental cues, rotifers can switch the mode of reproduction from parthenogenic reproduction to sexual reproduction, in which diploid sexual females are produced (Snell and Carmona, 1995). Diploid sexual females then produce haploid eggs through meiosis, which develop into haploid males or RE if fertilized by males (Preston et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation